2002
DOI: 10.1080/13674670110112749
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of medieval mysticism & hysteria

Abstract: This paper examines the historical association between medieval mysticism and asceticism and the psychopathological condition of hysteria. We rst review the particular forms of medieval mysticism and asceticism that seem to have inspired modern psychiatrists and reductive historians to dismiss these phenomena as indubitably neurotic behaviours. Then we review the concept of hysteria as it evolved during the last two centuries for points of convergence with mysticism. Finally, we question the validity of value-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This example highlights the existence of a widespread and popular idea that the experience of malign spiritual forces is closely related to insanity. Lipsedge (1996) and Kroll et al (2002) have shown that in medieval times demons and other malign spiritual forces were only occasionally seen as possible causes of psychiatric illness. Contemporary studies have examined beliefs that malign spiritual forces can be causes of insanity.…”
Section: Can We Distinguish Between Pathological and Benign Visions A...mentioning
confidence: 99%
“…This example highlights the existence of a widespread and popular idea that the experience of malign spiritual forces is closely related to insanity. Lipsedge (1996) and Kroll et al (2002) have shown that in medieval times demons and other malign spiritual forces were only occasionally seen as possible causes of psychiatric illness. Contemporary studies have examined beliefs that malign spiritual forces can be causes of insanity.…”
Section: Can We Distinguish Between Pathological and Benign Visions A...mentioning
confidence: 99%
“…While my focus is on what Lukoff () describes as ‘visionary spiritual experience’ (VSE), I seek to address the broader issue of the interrelationship between psychosis and religious experience. I fully recognize that it is immensely difficult to speak of ‘mysticism’ and I accept that there are, in fact, ‘no satisfactory definitions of mysticism’ (Kroll, Bachrach & Carey, , p. 84). Even when looking within the Christian tradition the notion of ‘Christian mystics’ as such is controversial (Bomford, , p. 177).…”
mentioning
confidence: 97%
“…The analytical aim of this paper on the other hand is to try and understand the extent to which the VSE of St Ġorġ Preca can be compared with the phenomenology of hallucinations and delusions in psychosis. In considering the experiences of mystics alongside psycho‐diagnostic categories one must be wary that the exercise does not end up ‘serving little purpose other than disparaging a group (both men and women) whose vision of what is valuable in life and worth struggling for differed radically from a materialistic and secular viewpoint’ (Kroll, Bachrach & Carey, , p. 92). VSE needs to be considered in light of the frame of reference that renders these experiences meaningful social realities.…”
mentioning
confidence: 99%